Double Narcissus from the collection of the Central Botanical Garden of the National Academy of Sciences of Belarus - Zavadskaya, Lyudmila; Kuzmenkova, Svetlana (Hortus botanicus, 2020)
Cultivars of Double Narcissus Group from the collection of the Central Botanical Garden of the the National Academy of Sciences of Belarus were evaluated. Their adaptive capability within the conditions of the republic was explored. Their ornamental, agricultural and biological qualities, resistance to abiotic and biotic environmental factors were evaluated. 35 cultivars from the collection fund were described. The perspective of Double Narcissus introduction to the conditions of central Belarus as an agricultural plant for amenity planting was determined.